ABCB1 polymorphisms influence the response to antiepileptic drugs in Japanese epilepsy patients. (June 2006) - Seo, Takayuki; Ishitsu, Takateru; Ueda, Nao; Nakada, Naoyuki; Yurube, Keigo; Ueda, Kentaro; Nakagawa, Kazuko
Objectives: The efflux transporter P-glycoprotein encoded by the ATP-binding cassette ( ABC)B1 gene may play a role in drug-resistant epilepsy by limiting gastrointestinal absorption and brain access of antiepileptic drugs (AEDs). Our objective was to investigate the effect of ABCB1 polymorphisms on AED responsiveness and on the pharmacokinetics of carbamazepine (CBZ) in epileptic patients with the indication for CBZ therapy.Methods: The ABCB1 T-129C, C1236T, G2677T/A and C3435T polymorphisms were genotyped in 210 Japanese epileptics who had been prescribed AEDs, including CBZ, for longer than 2 years. Haplotype and diplotype frequencies were estimated by expectation––maximization algorithm. Drug resistance was determined by the presence of seizures. Association of the polymorphisms with the risk of drug resistance was estimated by logistic regression analysis and the odds ratios (ORs) were adjusted for the clinical factors affecting the outcome of AED therapy. CBZ concentrations to the dose (C/D) ratios were compared among the ABCB1 polymorphisms.Results: Drug-resistant patients were more likely to have the T allele (OR [95% confidence interval (CI)], 2.02 [1.14––3.58]) and the TT genotype at C3435T (OR [95% CI], 3.64 [1.16––11.39]), and the TT genotype at G2677T/A (OR vs the GG genotype [95% CI], 3.43 [1.01––11.72]). The frequency of the T-T-T haplotype at C1236T, G2677T/A and C3435T was significantly higher (OR [95% CI], 1.84 [1.03––3.30]), and the CC-GG-CC diplotype was lower (OR [95% CI], 0.09 [0.01––0.85]) in the drug-resistant patients than in the drug-responsive patients. None of the ABCB1 polymorphisms were observed to influence the C/D ratios of CBZ.Conclusion: We demonstrated that ABCB1 polymorphisms may influence the AED responsiveness without significant changes in the plasma concentrations of CBZ. Our findings were the inverse of previous results in European epileptics, thus the influence of ABCB1 polymorphisms on the AED responsiveness and/or the P-glycoprotein activity may vary among races.